Scope and Challenges in Smart Glasses: A Comprehensive Study on Present Scenario - Boksha, Jufishan; Nath, Asoke (International Journal of Computer Sciences and Engineering, 2019)
Smart glasses are wearable computer glasses that display real-time information directly in front of users’ field of vision by using Augmented Reality (AR) techniques. Generally, they can also perform more complex tasks, run some applications, and support Internet connectivity and able to change their optical properties at runtime. There are various companies coming up with new varieties of smart glasses and also improvements are done on the existing ones. Google glasses is also an example of smart glasses. Smart sunglasses are also available, which are programmed to change tint by electronic means are an example of the latter type of smart glasses. In the present paper the author will present a detailed study of smart glasses and its working principle, developments, comparison between different smart glasses product, its benefits, risks, and also its future scope.